Risk Factors of Progression in Low-tumor Burden Follicular Lymphoma Initially Managed by Watch and Wait in the Era of PET and Rituximab. Issue 5 (26th May 2023) - Rodier, Cyrielle; Kanagaratnam, Lukshe; Morland, David; Herbin, Adélie; Durand, Amandine; Chauchet, Adrien; Choquet, Sylvain; Colin, Philippe; Casasnovas, René Olivier; Deconinck, Eric; Godard, François; Delmer, Alain; et al.
Abstract : Patients (pts) with asymptomatic low-burden follicular lymphoma (FL) are usually observed at diagnosis. Time to lymphoma treatment (TLT) initiation can however be very heterogeneous and risk factors of progression are poorly studied. Our study evaluated 201 pts with grade 1–3a low-tumor burden FL diagnosed in four French centers between 2010 and 2020 and managed by a watch and wait strategy in real-life settings. After a median follow-up of 4.8 years, the median TLT was 4.2 years (95% confidence interval, 3.1-5.5). On multivariate analysis, elevated lactate dehydrogenase (hazard ratio [HR] = 2.2; P = 0.02), more than 4 nodal areas involved (HR = 1.7; P = 0.02) and more than 1 extranodal involvement (HR = 2.7; P = 0.01) were identified as independent predictors of TLT. The median TLT was 5.8 years for pts with no risk factor, 2.4 years for 1 risk factor, and 1.3 years for >1 risk factors ( P < 0.01). In a subanalysis of 75 pts staged with positron emission tomography-computed tomography (PET-CT), total metabolic tumor volume (TMTV) ≥14 cm 3 and standardized Dmax (reflecting tumor dissemination) >0.32 m −1 were also associated with shorter TLT (HR = 3.4; P = 0.004 and HR = 2.4; P = 0.007, respectively). In multivariate models combining PET-CT parameters and clinical variables, TMTV remained independent predictor of shorter TLT. These simple parameters could help to identify FL patients initially observed at higher risk of early progression. The role of PET-CT (extranodal sites and PET metrics) in low-burden FL appears promising and warrants further assessment in large cohorts. Abstract :